Superior vena cava flow and intraventricular haemorrhage in extremely preterm infants. (18th May 2016) - Bates, Sarah; Odd, David; Luyt, Karen; Mannix, Paul; Wach, Richard; Evans, David; Heep, Axel
Abstract: Objective : To evaluate the relationship between superior vena cava flow (SVCF) measurements within the first 24 h of life, and development of intraventricular haemorrhage (IVH) in extremely preterm infants. Study design : Single centre retrospective cohort study of 108 preterm infants born less than 28 weeks' gestation. Main outcome measure was degree of IVH at day 7 postnatal age. Results : The mean GA of the study group was 25.4 weeks. Mean SVCF was lower (75 ml/kg/min) in infants later diagnosed with IVH ( n  = 46) compared to infants, who did not develop IVH (87.7 ml/kg/min, p  = 0.055). PDA diameter was inversely associated with SVCF ( p  = 0.024) and reversal of flow in the descending aorta ( p =  0.001). Sensitivity analysis did not confirm an independent association of SVCF with development of IVH [OR 0.990 (0.978–1.002), p  = 0.115]. Conclusion : Our study describes early SVCF in extremely preterm infants is associated with the extent of ductal shunting, but insensitive in predicting IVH.